The paris widow ebook - Belle, Kimberly (2024)
A dream vacation turns deadly when secrets from the past catch up to a married couple in Paris in this new edge-of-your-seat thriller from USA Today bestselling author, Kimberly Belle. When Stella met Adam, she thought she had finally found a nice, normal guy—a welcome change from her previous boyfriend and her precarious jetsetter lifestyle with him. But her secure world comes crashing down when Adam goes missing after an explosion in the city square. Unable to reach him, she panics. As the French police investigate, it's revealed that Adam was on their radar as a dealer of rare and stolen antiquities with a long roster of criminal clients. Reeling from this news, Stella is determined not to leave Paris until she has the full story. Was Adam a random victim or the target of the explosion? And why is someone following her through the streets of Paris? An irresistible, fast-paced read set in some of Europe's most inviting locales, The Paris Widow explores how sinister secrets of the past stay with us—no matter how far we travel. More gripping thrillers from Kimberly Belle: Dear Wife Stranger in the Lake My Darling Husband The Personal Assistant The Paris Widow